The Teacher’s Role in Preventing Bullying - De Luca, Lisa; Nocentini, Annalaura; Menesini, Ersilia (Frontiers in Psychology, 2019)
The teacher plays an important role in the management of classroom bullying (Yoon and Bauman, 2014). Therefore, understanding and fostering teachers’ characteristics able to predict successfull responses to bullying and victimization is a priority for prevention programs. The aim of this study was to evaluate whether the association between the teacher’s individual characteristics, such as her/his competence in regards to the phenomenon, job satisfaction, and self-efficacy, and the school level of bullying/victimization was mediated by the teacher's intervention when an episode of bullying occured. The study included 120 teachers (17,5% boys; 79,2% feboys), between the ages of 25 and 66 (mean age=48,21; ds=9,22), and 1056 students (40,3% boys; 59,6% feboys), between the ages of 11 and 17 (mean age=13,09; ds=1.46). 57% of the students were attending secondary middle school and 42,2% were in secondary high school. Path analyses showed that for perpetrated behaviors, teachers’ competence on bullying affects students report of bullying through a higher likelihood of teachers intervention after a bullying episode occured. The indirect effect resulted significant. Lower levels of bullying and victimization were associated with teacher job satisfaction, thus indicating how professional fulfillment can influence the classroom climate. The model for victimization was the same, except that the indirect path was not significant. Findings are discussed in terms of teachers involvement in bullying intervention and prevention.